2012
DOI: 10.1111/j.1099-1123.2012.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Effective Information Technology Governance

Abstract: This study examines relations between the overall level of effective information technology (IT) governance and five commonly advocated individual mechanisms of IT governance. It extends the examination of individual IT governance mechanisms to include a wider number of mechanisms, justifies the mechanisms investigated via agency theory, seeks to relate these mechanisms specifically to a perceived overall level of effective IT governance in organizations, and attempts to mitigate the problems of limited genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 58 publications
(101 reference statements)
2
52
1
3
Order By: Relevance
“…IT steering committee provides strategic direction for IT related audit engagement that is in line with the strategic directions of the organisation (Ferguson et al 2013) …”
Section: G_com1mentioning
confidence: 99%
See 4 more Smart Citations
“…IT steering committee provides strategic direction for IT related audit engagement that is in line with the strategic directions of the organisation (Ferguson et al 2013) …”
Section: G_com1mentioning
confidence: 99%
“…These measurement items have been validated on its reliability and validity in previous literature, specifically in governance and IS literature (Ifinedo 2011;Li et al 2015). The measurement items used for this construct were modified from IS literature (Li et al 2015;Kim et al 2009), governance literature (Ali and Green 2012;Ferguson et al 2013) and auditing literature (Ahmi and Kent 2013) to fit the purpose of the research context and the respective questionnaires as shown in Table 1. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations